2020
DOI: 10.1563/aaid-joi-d-19-00191
|View full text |Cite
|
Sign up to set email alerts
|

Successful Management of Dental Implants in Postoperative Maxillary Cyst: A Case Report With a 13-Year Follow-Up

Abstract: The report is presenting a case of implant placement in the postoperative maxillary cyst (POMC) with a follow-up of 13 years. The POMC is a complication associated with various surgical interventions involving maxillary sinus diseases such as Caldwell-Luc operation, orthognathic surgery, and sinus grafting procedures. The lesion of POMC is believed to develop as a result of the changes of ciliated cells or the blockage of ostia inside the maxillary sinus. Two dental implants were placed near the lesion that wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…So far, the Caldwell-Luc technique or lateral window technique [29] has been reported to cause greater surgical invasion and the occurrence of a postoperative cyst [23,27,49,56,57]. However, ES is less surgically invasive and less likely to cause postoperative cysts [27,58].…”
Section: Discussionmentioning
confidence: 99%
“…So far, the Caldwell-Luc technique or lateral window technique [29] has been reported to cause greater surgical invasion and the occurrence of a postoperative cyst [23,27,49,56,57]. However, ES is less surgically invasive and less likely to cause postoperative cysts [27,58].…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, we would suspect that a residual odontogenic cyst owing to incomplete removal during tooth extraction might migrate into the maxillary sinus. Some reports have described patients with POMC whose dental implant was successfully preserved via the enucleation of the POMC [8] , [9] , [10] , [11] , while in others, the preservation of the dental implant by the enucleation of both the POMC and the implant close to the POMC was impossible [12] , [13] . Thus, debate still exists as to whether the preservation of the dental implant close to the POMC is possible via enucleation.…”
Section: Discussionmentioning
confidence: 99%
“…In a literature analysis of the PubMed database (key words: Marsupialization OR Partsch AND implant; Cyst AND dental implant; Cyst AND endosseus implant; Cyst AND impacted implant; Partsch AND dental implant), only a few case reports about implants impacted in a maxillary cyst can be found. Park et al, in an infected postoperative maxillary cyst, performed cystectomy, implant conservation, decontamination, and bone grafting to fill the defect [20]. Other authors have reported cases of nasopalatine duct cysts impacted in dental implants.…”
Section: Discussionmentioning
confidence: 99%
“…However, they raised concerns about the possible defect size following enucleation and possible need for bone grafting [11]. Some authors have recommended titanium brushing to debride and mechanically decontaminate implant surfaces and suggested the use of antibiotics and chemical decontamination, although the literature seems inconclusive on this operative protocol [20,[33][34][35]. The authors also decided not to follow through these procedures since the cyst wall seemed intact and presumably absolved a barrier function between implants and cyst cavity, and the surgical access did not allow it.…”
Section: Discussionmentioning
confidence: 99%